Improving Student Creativity Through the Use of Smart Card-Based Learning Media - Jayadi Jayadi; Rian Aldi Wardana; Ilham Albizar Fisthan; Aqib Luqman Hidayat; Sudarmono Sudarmono (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study was motivated by the low level of creativity in the learning process among eighth-grade students at SMP Negeri 9 Sampit. The teaching methods used remain one-sided and rely heavily on textbooks, leaving little room for students to explore and develop their own ideas. The objective of this study is to enhance student creativity through the use of smart card learning media that integrates digital links, contextual case studies, and summaries of course material. A Classroom Action Research (CAR) design, employing a descriptive quantitative approach based on the Kemmis and McTaggart cycle model, was utilized. The study was conducted in two cycles, with three sessions in each cycle. All 27 eighth-grade students participated as research subjects. Based on Munandar’s four affective indicators of creativity—curiosity, imagination, willingness to take risks, and respect for others’ opinions—observation sheets and creativity questionnaires were used to collect data. The research results show that the average creativity score increased gradually, from 2.2 in the pre-cycle to 2.8 in Cycle I and 3.3 in Cycle II, exceeding the minimum success criterion of 3.0. The “willingness to take risks” indicator received the highest score of 1.5 points, and the “curiosity” indicator received the highest score of 3.7 at the end of Cycle II. This success was found to be influenced by reflective improvements made in each cycle, which included enhancements to the game mechanics, group role assignments, and targeted motivation. This study found that smart cards effectively enhance student creativity. The results indicate that smart cards can serve as an inventive alternative for teaching social studies and other subjects.